Manajemen Kinerja Berbasis Kompetensi di Era Digital pada Telkom Maumere - Apriliana Ovin; Yasinta Flarida Erviana; Magdalena Oktaviani; Maria Silvana Mariabel Carcia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the implementation of competency-based performance management in the digital era at Telkom Maumere. Amid the ongoing digital transformation, organizations are required to enhance employee performance through structured systems that are adaptive to technological changes. Competency-based management has become a key strategy to ensure that every individual possesses the skills and behaviors aligned with organizational goals. This research employs a qualitative descriptive approach with data collected through interviews, observations, and document analysis. The findings indicate that Telkom Maumere has adopted a performance management system integrated with digital technologies, such as the use of e-performance applications and online evaluation systems. However, challenges remain in terms of digital training and comprehensive competency mapping. The study concludes that competency-based performance management in the digital era can enhance work productivity, provided it is supported by adequate technological infrastructure and an adaptive organizational culture.